Brivaracetam Population Pharmacokinetics and Exposure‐Response Modeling in Adult Subjects With Partial‐Onset Seizures. (7th June 2016) - Schoemaker, Rik; Wade, Janet R.; Stockis, Armel
Abstract: Brivaracetam is a selective high‐affinity ligand for synaptic vesicle protein 2A, recently approved as adjunctive therapy in the treatment of partial‐onset (focal) seizures in patients 16 years of age and older with epilepsy. A population pharmacokinetic (PK) model and a population pharmacokinetic/pharmacodynamic (PKPD) model were developed describing brivaracetam plasma concentration and the relationship with daily seizure counts in adequate well‐controlled efficacy trials. The effect of body weight on clearance and volume was implemented using allometric scaling, and a range of covariates were investigated for their influence on brivaracetam clearance. The PKPD model described daily seizure counts using a negative binomial distribution, taking previous day seizures into account, and using a mixture model to separate "placebo‐like" and "response" subpopulations. The PK and PKPD models provided a good description of the data, documented using visual predictive checks. Coadministration with carbamazepine, phenytoin, and phenobarbital decreased brivaracetam exposure by 26%, 21%, and 19%, respectively, without significant effects on PD response. Covariate analysis indicated that levetiracetam coadministration reduced the fraction of subjects in the mixture model response population to 4% and identified baseline seizure frequency as a strong predictor for being assigned to the mixture model response population. Simulation allowed characterization of the dose‐response curve, suggesting maximum response is obtained at brivaracetam 150–200 mg/day.